2018
DOI: 10.1089/dna.2017.4029
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Facilitates the Survival and Proliferation of Nucleus Pulposus Cells in TNF-α Stimulus by Activating Unfolded Protein Response

Abstract: Intervertebral disc (IVD) degeneration is closely related to inflammatory cytokines, such as tumor necrosis factor alpha (TNF-α). The endoplasmic reticulum (ER) serves several important cell functions, which are essential for normal cell metabolism and survival. This study aims to clarify the role of ER stress and unfolded protein response (UPR) in TNF-α-induced biological changes in rat nucleus pulposus cells (NPCs) and IVD degeneration. In our research, rat NPCs were cultured with different concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
1
19
0
2
Order By: Relevance
“…Common inducers of inflammatory responses in the IVD, IL-1β and TNF-α, were previously shown to activate ER stress in IVD cells ( 35 ): 10 ng/mL TNF-α upregulated ER stress markers and initiated UPR in rat IVD cells ( 36 ), while 75 ng/mL IL-1β activated gene and protein expression of ER stress markers (including GRP78 and CHOP) in human primary IVD cells ( 37 ). However, in our study, IL-1β and TNF-α did not induce a prolonged ER stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Common inducers of inflammatory responses in the IVD, IL-1β and TNF-α, were previously shown to activate ER stress in IVD cells ( 35 ): 10 ng/mL TNF-α upregulated ER stress markers and initiated UPR in rat IVD cells ( 36 ), while 75 ng/mL IL-1β activated gene and protein expression of ER stress markers (including GRP78 and CHOP) in human primary IVD cells ( 37 ). However, in our study, IL-1β and TNF-α did not induce a prolonged ER stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ERK1/2 activation is believed to play a critical role in hASM proliferation induced by inflammatory cytokines (Lee et al, 2001;Kip et al, 2005;Yu et al, 2013;Dragon et al, 2014;Movassagh et al, 2014). While the relation between ER stress and Mfn2 is not clearly established, studies suggest that ER stress induces cell proliferation in many cell types (Vandewynckel et al, 2013;Chen et al, 2018). Whether ER stress induces hASM cell proliferation is unknown.…”
Section: Role Of Mfn2 In Hasm Cell Proliferationmentioning
confidence: 99%
“…To address the high burden of IDD and related conditions, many studies have focused on maintaining the number of nucleus pulposus cells (NPCs) and enhancing the deposition of functional components of the extracellular matrix (ECM) [8]. To this end, the potential of mesenchymal stem cells (MSCs), represented as progenitor NPCs in the NP, has been intensively explored in the field of IDD research [9, 10, 20]. Whereas in intact discs the annulus fibrosus that surrounds the NP limits the differentiating potential of MSCs [11], in vitro experiments showed that activated MSC clusters react to pro-inflammatory stimuli by releasing anti-inflammatory factors [12, 13] and influence paracrine coordination of cell cycle, to delay or even reverse aging at both cellular and organismal levels [14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research has shown that MSCs can influence NPC survival and function through paracrine effects involving the release of soluble cytokines and extracellular vesicles [1517]. Investigations also showed differential NP gene expression in IDD models in response to stress-related processes such as aging [18], oxidation [19], the unfolded protein response [20], and metabolism [21].…”
Section: Introductionmentioning
confidence: 99%